External allies, financing and autonomy of agroecological processes. The experience of the Agroecological Fund for the Yucatan Peninsula, Mexico - Giraldo, Omar Felipe (2025)
The transition to agroecology faces significant challenges due to dependence on traditional philanthropic models and the many harmful effects of their funding approaches. The Agroecological Fund for the Yucatan Peninsula (FAPY), in Mexico, is proof that it is possible to change the support practices from external partners and modify the relationships between actors. FAPY is an innovative fund that promotes agroecology while respecting the Mayan communities’ autonomy and knowledge. Led by indigenous actors, this fund prioritizes flexibility, participation and trust, and directs its strategies toward reducing colonial or paternalistic practices. FAPY facilitates access to resources through accessible calls for proposals, and encourages self-determination by allowing communities to decide how to use them according to their needs. This article shows how the funded projects are contributing to strengthening local agroecological practices, food sovereignty, climate resilience, and creativity in production. In addition, FAPY seeks to consolidate decentralized governance and support based on trust, prioritizing knowledge dialogue and strengthening local capacities. This approach contrasts with vertical models, demonstrating that it is possible to promote respectful and inclusive agroecological transitions that strengthen community autonomy and reinforce internal capacities.